Pengaruh Pemberian Pupuk Daun dan Pemangkasan Terhadap Produksi Belimbing (Averhoa carambola L.): Effect Of Foliar Fertilizer and Pruning on The Production of Star Fruit (Averhoa carambola L.) - Dwi Haryanta (Agrocentrum, 2023)
Flower and fruit loss and low fruit quality are complex problems faced in star fruit cultivation. The research aims to determine the effect of pruning twigs and applying foliar fertilizer on plant growth, quantity and quality of fruit. Factorial research using two treatment factors. . Factor I is the type of foliar fertilizer, consisting of D0 = No foliar fertilizer (control), D1 = SB foliar fertilizer (8-20-15), D2 = HP foliar fertilizer (10-40-15), and D3 = DN foliar fertilizer (10-30-37). Factor II is the interval for applying foliar fertilizer, consisting of I1 = once every 7 days interval, I2 = once every 10 days interval, and I3 = once every 14 days interval. The research used plant material of the same age, as replications, groups of plants were used that were differentiated according to the pruning model, namely P0 = Plants that were not pruned as replication I, P1 = Plants that only had their wiwilan branches pruned as replication II, and P2 = Plants that had their branches pruned wiwilan and clustered branches (remaining the good ones) as repetition III. The results showed that application of foliar fertilizer and pruning of branches increased the number of fruit, fruit weight and size of sweet star fruit. Pruning wiwilan branches and reducing clustered branches has the greatest effect on the number of fruit, fruit weight and fruit volume compared to other pruning intensities. The research results can be used as a reference for star fruit farmers in determining maintenance actions, especially in fertilizing and pruning to regulate the canopy. while increasing production.